Diastolic blood pressure impact on pediatric refractory septic shock outcomes - En-Pei Lee; Chen-Wei Yen; Ming-Shun Hsieh; Jainn-Jim Lin; Oi-Wa Chan; Ya-Ting Su; Chun-Ting Mu; Han-Ping Wu; Shao-Hsuan Hsia (Elsevier, 2024)
Background: Septic shock is the progression of sepsis, defined as cardiovascular dysfunction during systemic infection, and it has a mortality rate of 40 %-80 %. Loss of vascular tone is an important pathophysiological feature of septic shock. Diastolic blood pressure (DBP) was reported to be associated with vascular tone. This study aimed to identify the associations of several hemodynamic indices, especially DBP, with outcome in pediatric septic shock to allow for timely interventions. Methods: Children with persistent catecholamine-resistant shock had a pulse index continuous cardiac output (PiCCO®) system implanted for invasive hemodynamic monitoring and were enrolled in the current study. Serial cardiac index, systemic vascular resistance index (SVRI), systolic blood pressure (SBP), mean arterial pressure (MAP), and DBP were recorded during the first 24 h following PiCCO® initiation. All hemodynamic parameters associated with 28-day mortality were further analyzed using receiver operating characteristic curve analysis. Results: Thirty-three children with persistent catecholamine-resistant shock were enrolled. The median age was 12 years and the youngest children were 5 years old. Univariate analysis noted that SVRI, SBP, MAP, and DBP were significantly higher, and shock index was significant lower, in survivors compared with non-survivors (p < 0.05). In the multivariate analysis, only SVRI and DBP remained independent predictors of 28-day mortality. DBP had the best correlation with SVRI (r = 0.718, n = 219, p < 0.001). The area under the receiver operating characteristic curves of SVRI and DBP for predicting 28-day mortality during the first 24 h of persistent catecholamine-resistant shock were >0.75, indicating a good prediction for mortality. Conclusions: DBP correlated well with SVRI and it can serve as a predictor for mortality in pediatric septic shock. Furthermore, DBP was a superior discriminator of mortality when compared with SBP and MAP. A lower DBP was an independent hemodynamic factor associated with 28-day mortality.